2004
DOI: 10.1093/019924488x.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Political Choice in Britain

Abstract: Political Choice in Britain uses data from the 1964 to 2001 British election studies (BES), 1992 to 2002 monthly Gallup polls, and numerous other national surveys conducted over the past four decades to test the explanatory power of rival sociological and individual rationality models of electoral turnout and party choice. Analyses endorse a valence politics model that challenges the long-dominant social class model. British voters make their choices by evaluating the performance of parties and party leaders i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
326
1
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 718 publications
(344 citation statements)
references
References 160 publications
11
326
1
6
Order By: Relevance
“…They concluded that ''partisanship is fundamentally connected to notions of performance'' (Clarke et al 2004:316). This is in line with Smith's (2001) view of the political brand, as it provides a heuristic on capability to deliver the political brand promise on valence issues and, according to Clarke et al (2004), will then be able to generate brand or party loyalty. The relationship consumers have with a brand has been explored in a number of ways; there is extensive literature on brand loyalty that has been extended by Fournier (1998), who suggests that a more fruitful alternative to brand loyalty would be ''brand relationship quality.''…”
Section: Brandingsupporting
confidence: 62%
See 1 more Smart Citation
“…They concluded that ''partisanship is fundamentally connected to notions of performance'' (Clarke et al 2004:316). This is in line with Smith's (2001) view of the political brand, as it provides a heuristic on capability to deliver the political brand promise on valence issues and, according to Clarke et al (2004), will then be able to generate brand or party loyalty. The relationship consumers have with a brand has been explored in a number of ways; there is extensive literature on brand loyalty that has been extended by Fournier (1998), who suggests that a more fruitful alternative to brand loyalty would be ''brand relationship quality.''…”
Section: Brandingsupporting
confidence: 62%
“…But they can be wrong (Lakoff 2004;MacKuen and Parker-Stephen 2006); they can misunderstand the issue and also misunderstand which party holds the position closest to their own position (Kuklinski et al 2000). The valence model was first articulated by Stokes (1969, 1974) and developed further by Clarke et al (2004), who argued that citizens focused upon universal issues such as health, crime, and the economy. They claimed that voters did not think about politics on a regular basis and made ''rough and ready'' judgments (Clarke et al 2004: 326) based upon heuristic devices such as party leaders.…”
Section: Brandingmentioning
confidence: 99%
“…This exercise is designed to establish benchmark models of the relationships which can subsequently be compared with equivalent models for the Coalition government. The analysis is based on the valence model of electoral choice, which has been extensively developed by the authors in recent publications (Clarke et al 2004Whiteley et al 2013). In a subsequent section these models are estimated for the period of the Coalition government from May 2010 to March 2014.…”
Section: This Was a Popular Message At The Time The June 2010 Britismentioning
confidence: 99%
“…This approach has the advantage of estimating dynamic effects and it tends to average out the noise associated with individual level models of the vote. On the other hand economic voting models using individual cross-sectional or panel data can include many more variables, so the models are more extensively specified (Butler and Stokes, 1969;Clarke et al 2004Whiteley, 2013). This is because aggregate analyses are subject to significant data limitations, both in terms of the number of observations and also the availability of measures over time.…”
Section: The Relationship Between the Economy And Votingmentioning
confidence: 99%
“…1 Las investigaciones empíricas en ciencia política han acumulado una serie de variables en torno a la decisión del voto, las cuales comprenden tanto de factores de largo como de corto plazo (Miller y Niemi, 2002), incluyendo las características sociodemográficas (Lazarsfeld et al, 1948;Lipset, 1987), la identificación partidaria (Campbell et al, 1960), la proximidad ideológica (Downs, 1957), la evaluación gubernamental (Fiorina, 1981) y económica (Lewis-Beck y Stegmaier, 2007, Lewis-Beck y Stegmaier, 2013), los temas (issues) de valencia y posición (Stokes, 1963) y los efectos de líderes y campañas (Bartels, 2002;Dilliplane, 2014;Iyngar y Simon, 2000;Lawson et al, 2010). Varios trabajos han asumido enfoques multifactoriales en los cuales las distintas variables se disputan por proveer el máximo potencial explicativo, por ejemplo en elecciones de Estados Unidos (Clarke, et al 2015), Italia (Bellucci y Segatti, 2010), Reino Unido (Clarke et al, 2004) y América Latina (Carlin, Singer, y Zechmeister, 2015;Nadeau et al, 2017).…”
Section: Introductionunclassified